Sequencing BCMA- and GPRC5D-targeting immunotherapies in multiple myeloma: practical guidance from the European Myeloma Network - Donk, Niels van de; Moreau, Philippe; San-Miguel, Jesus F.; Mateos, Maria-Victoria; Dimopoulos, Meletios A.; Zweegman, Sonja; Gay, Francesca; Engelhardt, Monika; Mina, Roberto; Zamagni, Elena; Delforge, Michel; Beksac, Meral; et al. (HemaSphere, 2025)
The treatment landscape of heavily pretreated relapsed/refractory MM has changed considerably in recent years with the introduction of novel BCMA- and GPRC5D-directed immunotherapies, including CAR T-cell therapy, bispecific antibodies (BsAbs), and antibody-drug conjugates (ADCs). Treatment selection and sequencing become increasingly complex with the broad range of therapeutic options. In this review, the European Myeloma Network provides recommendations on how to best incorporate these novel therapies into the present treatment landscape using current evidence. The optimal treatment sequence depends on various patient- and tumor-related features, but also reimbursement and availability issues. In addition, mechanisms underlying relapse (e.g., antigen loss, reduced T-cell fitness, or outgrowth of T-cell resistant clones) dictate the efficacy of sequential BCMA- or GPRC5D-directed immunotherapy. BCMA-targeting BsAbs and ADCs should preferably be avoided prior to CAR T-cell therapy, as some studies have shown that these agents negatively influence clinical outcomes after CAR T-cell therapy. Therefore, we recommend the selection of CAR T-cell therapy first, and BsAbs and/or belamaf later in the disease course, if patients are eligible for CAR T-cell therapy and in case CAR T-cell therapy is available within a short time frame. However, bridging therapy with GPRC5D-directed BsAbs (initiation after apheresis) can be considered to significantly reduce tumor burden, because this was shown to improve the efficacy of consecutive BCMA-directed CAR T-cell therapy. Sequential treatment with agents targeting the same antigen, but with different modes of action, is feasible, but several studies have demonstrated that target switch is a more effective strategy. In addition, there is increasing evidence indicating that the efficacy of sequential use of BsAbs can be improved by creating a BsAb-free interval.
Zuerst veröffentlicht: 25. November 2025
Gesehen am 30.01.2026